ARSITEKTUR HUNIAN SUKU DAYAK BUKIT (Kajian atas perubahan dan keragaman dengan pendekatan etnografi) - , Bani Noor Muchamad, Prof. Ir. Tony Atyanto Dharoko, M.Phil., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research originated from the change and the typology of balai-adat as a traditional dwelling of Dayak Bukit tribes. Through field observation, it has been identified the change and the typology of space and form. However, base to the textual and literature study, it does not find an explanation of the change of space and form of balai-adat. For that reason, if the various changes of balai-adat that occur is an effort of Dayak Bukit to meet the needs of the space as their way of life, why so far was not adequate explanation to this phenomenon. It is the research problem. To answer, it was formulated the following research questions. (1) What are the changes and the typology of the space and form of Dayak Bukitâs dwelling? (2) What is the influence of the change and the typology concerning to the knowledge of Dayak Bukitâs dwelling? (3) What are the symbols and the meaning of the phenomenon of the Dayak Bukitâs dwelling? This research utilized naturalistic paradigm based on the axioms of the nature of reality. By focusing the study on local people in developing and building their living tradition, this research employed ethnography method. By data induction of balai-adat's space and form was found an explanation, as interpretation, about the change, which included an overview, the factors affecting changes and the process, the categories, and the themes. Next, these interpretations were analyzed to figure out concepts of Dayak Bukitâs dwelling which contains the concepts of balai-adat and bubuhan. The concept of balai-adat describes the nucleus space and the process of extended space. The concept of bubuhan explains both of the kinship system in the influence of the aspect of space-forms of the Dayak Bukitâs dwelling, and the kinship system in the changes of dwelling and living tradition. Both of the concepts of balai-adat and the concepts of bubuhan are the substance of Dayak Bukit's dwelling concept.